EFEKTIVITAS VIRTUAL LAB TERINTEGRASI PHET BERBASIS STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PERSAMAAN REAKSI - Gusman, Tania Avianda; Simanjuntak, Sara Angelica; Putri, Vania Hardianti; Saroah, Saroah (LPPM Universitas Bina Bangsa, 2025)
Chemical reaction equations are still a difficult topic for some students to understand. Based on interviews with the grade X teacher at SMAN 1 Sumber, it was found that most students struggled to grasp the concept of chemical reaction equations. This was evident from the low average student scores in the previous academic year, which was 60—still below the minimum passing grade (KKM). Therefore, this study was conducted to examine the effectiveness of the Cooperative Learning model STAD in improving student learning outcomes on the topic of chemical reaction equations. The research used a non-equivalent control group design, with samples taken from class X.1 and X.7 totaling 35 students. The results of the study showed a significant improvement in learning outcomes through the use of a STAD-based virtual lab, with an average score of 74.14. Meanwhile, the N-Gain score reached the moderate category at 0.64, indicating the effectiveness of the Virtual Lab-integrated STAD model using PhET in enhancing students' learning outcomes.